2008
DOI: 10.1177/0146167208323600
|View full text |Cite
|
Sign up to set email alerts
|

The Other Side of We: When Outgroup Members Express Common Identity

Abstract: Previous research on the common ingroup identity model has focused on how one's representations of members of the ingroup and outgroup influence intergroup attitudes. Two studies reported here investigated how learning how others, ingroup or outgroup members, conceive of the groups within a superordinate category affects intergroup bias and willingness to engage in intergroup contact. Across both studies, high school students who learned that other ingroup members categorized students at both schools within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 37 publications
(60 reference statements)
5
49
0
Order By: Relevance
“…The reactance effect is not unprecedented for group members’ responses to criticism from an outgroup member (Hornsey 2005) or proposed policy from a different political party (Cohen 2003; Gómez et al 2008). This highlights the risks and challenges of interventions to increase tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactance effect is not unprecedented for group members’ responses to criticism from an outgroup member (Hornsey 2005) or proposed policy from a different political party (Cohen 2003; Gómez et al 2008). This highlights the risks and challenges of interventions to increase tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…It is less obvious how a positive message of tolerance could have the same effect. An outgroup member's message of tolerance may be perceived as a negative judgment of the perceiver's present moral status, rather than as a universal message of compassion (Gómez et al 2008). Perceivers might be especially sensitive to an implied moral criticism when an outgroup member delivers a moral message—“Why else would he be telling me this unless he thought I was not tolerant?” In that sense, from the perceivers’ perspective, an outgroup member does not have the proper “credentials” to deliver moral messages, even with a positive framing.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, previous work has shown that when important identities or subgroup identities are neglected, individuals respond by increasingly affirming these identities, also resisting the expression of identification with-and loyalty to-other or superordinate identities (Barreto & Ellemers, 2002). Respect versus neglect of (sub)group identities has been found to decrease intergroup bias and increase identification with a larger (superordinate) social group (e.g., Barreto & Ellemers, 2002;Gaertner, Rust, Dovidio, Bachman, & Anastasio, 1994;Gomez, Dovidio, Huici, Gaertner & Cuadrado, 2008;Gonzalez & Brown, 2003;Hornsey & Hogg, 2000a;Huo, Smith, Tyler, & Lind, 1996;Jetten, Schmitt, Branscombe, & McKimmie, 2005). Similar evidence for the importance of outgroup attitudes for members of low-status (sub)groups can be found in work on acculturation (Bourhis, Moise, Perreault, & Senecal, 1997).…”
Section: Respect For Ingroup Domainsmentioning
confidence: 99%
“…Research guided by the Common Ingroup Identity Model (Gaertner & Dovidio, 2000) has demonstrated that inducing members of different groups to conceive of themselves in terms of a shared superordinate (one-group) identity improves intergroup attitudes (Gaertner & Dovidio, 2000) and increases motivations for intergroup contact (Gómez, Dovidio, Huici, Gaertner, & Cuadrado, 2008). However, it is also possible for people to recognize and endorse distinct subgroup identities within a superordinate identity: a "dualidentity" representation.…”
mentioning
confidence: 99%